2011
DOI: 10.1093/jxb/err058
|View full text |Cite
|
Sign up to set email alerts
|

Functional evolution of C4 pyruvate, orthophosphate dikinase

Abstract: Pyruvate,orthophosphate dikinase (PPDK) plays a controlling role in the PEP-regeneration phase of the C(4) photosynthetic pathway. Earlier studies have fully documented its biochemical properties and its post-translational regulation by the PPDK regulatory protein (PDRP). However, the question of its evolution into the C(4) pathway has, until recently, received little attention. One assumption concerning this evolution is that changes in catalytic and regulatory properties of PPDK were necessary for the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 43 publications
5
79
0
Order By: Relevance
“…Previous studies have shown that PPDK activity is strictly and reversibly regulated by light. This light/dark modulation is mediated by reversible phosphorylation of a conserved Thr residue in the active-site domain by PDRP Roeske and Chollet, 1987;Burnell and Chastain, 2006;Chastain et al, 2011). Nonetheless, if phosphorylation of PPDK at the active-site Thr serves only as an on/off switch tightly regulated by light/dark, then full activation of PPDK would occur at very low light intensity and would be much lower than that required for maximum rates of photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that PPDK activity is strictly and reversibly regulated by light. This light/dark modulation is mediated by reversible phosphorylation of a conserved Thr residue in the active-site domain by PDRP Roeske and Chollet, 1987;Burnell and Chastain, 2006;Chastain et al, 2011). Nonetheless, if phosphorylation of PPDK at the active-site Thr serves only as an on/off switch tightly regulated by light/dark, then full activation of PPDK would occur at very low light intensity and would be much lower than that required for maximum rates of photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…PPDK regulatory protein (PDRP), a unique bifunctional enzyme, catalyzes this light-dependent regulation by reversible phosphorylation of an active-site Thr in PPDK (Thr-527 in maize [Zea mays] in full amino acid sequence [http://www. maizegdb.org]; previously termed Thr-456; Ashton and Hatch, 1983;Burnell and Hatch, 1985;Roeske and Chollet, 1987;Ashton et al, 1990;Burnell, 1990;Chastain et al, 2000Chastain et al, , 2011. PDRP is an unusual regulatory protein for three reasons (Chastain et al, 1997(Chastain et al, , 2008Burnell and Chastain, 2006;Astley et al, 2011): (1) it is bifunctional, catalyzing both PPDK activation/dephosphorylation and PPDK inactivation/phosphorylation; (2) it uses ADP instead of ATP as the phosphoryl donor; and (3) it employs an inorganic phosphate-dependent, inorganic pyrophosphate-forming dephosphorylation mechanism as opposed to the simple hydrolysis mechanism common to most protein phosphatases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is invariably localized to the chloroplasts with the pyruvate phosphate dikinase (also known as pyruvate orthophosphate dikinase) as the central enzyme [4,[21][22][23]. It produces PEP, pyrophosphate (PP) and adenosine monophosphosphate (AMP) from pyruvate, phosphate and ATP.…”
Section: Modules Of the C 4 Cyclementioning
confidence: 99%
“…Many enzymes functioning in C4 photosynthesis, which play important metabolic roles in C3 plants (Aubry et al, 2011), have undergone specific changes in their amino acid sequence and correspondingly in their catalytic properties during their cooption into C4 photosynthesis; that is, the homologs used in C4 photosynthesis differ from their C3 homologs (Engelmann et al, 2003;Aubry et al, 2011;Chastain et al, 2011;Maier et al, 2011). Thus far, it is unclear how much difference introducing the C4 homologs versus using the endogenous C3 homologs might have on the photosynthetic CO 2 uptake rate and nitrogen use efficiency during C4 engineering.…”
Section: Significance Of Different Enzymes To C4 Photosynthetic Efficmentioning
confidence: 99%